CROWDFUNDING AS A NEW ALTERNATIVE OF FUNDRAISING FOR ENTREPRENEURSHIP ACTIVITIES IN HIGHER EDUCATION INSTITUTIONS - Abdullah Siti Salwani; Mukhtar Dzulkifli; Abdullah Azwan; Abdullah Ahmad Ridhuwan (International Journal of Accounting, Finance and Business, 2022)
Crowdfunding is a technique that utilizes incremental financial contributions from a 'crowd' of participants to assist entrepreneurs in funding their projects. Crowdfunding serves as a new entrepreneurial finance tool that enables entrepreneurs to access capital more easily. The purpose of this article is to examine a crowdfunding as a tool for entrepreneurship education in Malaysian higher education institutions (HEI). This study aims to better understand the mechanisms underlying the new novel concept of online funding known as crowdfunding by highlighting the crowdfunding activity continuum. Based on prior real-world crowdfunding experiences, which demonstrate how people are progressively supporting and adopting crowdfunding, the potentials of crowdfunding are far greater than anyone anticipated. Early-stage entrepreneurs, particularly those in higher education, benefit greatly from the visibility and financial options provided by crowdfunding since it allows them to fine-tune their concepts, make improvements, and gain experience working with potential backers. To begin, the study discusses the main activities of crowdfunding for entrepreneurship education in Malaysian HEI: (i) pre-crowdfunding activity and (ii) post-crowdfunding activity. Next, within the two broad crowdfunding activities for entrepreneurship education, there are five phases of crowdfunding activities: (i) phase 1: continuous practice when implementing crowdfunding, (ii) phase 2: embrace the use of crowdfunding and nurture it as the culture of the institution, (iii) phase 3: build a strong organizational structure, and support, for the use of crowdfunding as a new source of financing, (iv) phase 4: continuous reviews of current practices, (v) phase 5: continuous monitoring on each level of the organizational hierarchy. Finally, this study discussed the impact of crowdfunding which relates to the current situation and current government campaign which is Value-Based Intermediation (VBI). This study suggests that future research could focus on different study contexts (i.e., secondary education) in Malaysia or other developing countries